DESIGN AND MANUFACTURED OF LOG PERIODIC DIPOLE ARRAY (LPDA) ANTENNA AT 400 MHz - 800 MHz FREQUENCY AND ITS IMPLEMENTATION ON TELEVISION ANTENNA - Gozal Nur Ramaditya; Yulisdin Mukhlis (Merdeka Malang University, 2019)
In this study the designed Log-Periodic Dipole Array antenna (LPDA) in the frequency range 400 MHz up to 800 MHz with 7dBi Gain. For the purpose of point to point communication required antenna that has directivity and for wideband telecommunication system required a wideband type antenna. At a gain of 7 dBi, the wider the frequency range then the total length of the Log-Periodic Dipole Array (LPDA) antenna structure is also longer. The design of the Log-Periodic Dipole Array (LPDA) antenna operates at λ / 2 in the 400 MHz - 800 MHz frequency range and has the ideal VSWR value (VSWR ≈ 1) so that the antenna and transmission line are matched. The advantages of the Log-Periodic Dipole Array (LPDA) antenna itself is to have a wide bandwidth and geometry value following a certain comparison.DOI : https://doi.org/10.26905/jeemecs.v2i2.3126